Exploring the feasibility, acceptability, and safety of a real-time cardiac telerehabilitation and tele coaching programme using wearable devices in people with a recent myocardial infarction - A. Mitropoulos; Μ. Anifanti; G. Koukouvou; Α. Ntovoli; K. Alexandris; Evangelia Kouidi (BMC, 2024)
Abstract Background Cardiac rehabilitation (CR) constitutes the recommended nonpharmacological approach for cardiac patients with cardiovascular disease such as people following a recent (i.e., < 4 week) myocardial infarction (MI). Recent evidence suggests that cardiac telerehabilitation may be as effective as traditional (i.e., in person) CR in people following a recent MI. Nevertheless, the feasibility, acceptability, and safety of such an exercise programme has yet to be examined. Methods Forty-four (11 women, 33 men) people following a recent MI were randomly allocated into two groups (online home-based and gym-based groups). The groups underwent a 24-week CR programme thrice per week. All patients performed the baseline, and 24 weeks follow up measurements where feasibility, acceptability, and safety were assessed. Results Eligibility and recruitment rates were found to be 61.5% and 42%, respectively. Compliance to the thrice weekly, 24-week exercise programme for the online- and gym-based groups were 91.6% and 90.9%, respectively. There were no dropouts during the exercise programmes, however four participants, two from each group, were lost to follow up at 6 months. The average percentage of peak HR (% HRpeak) for the online group was 66.6% ± 4.5 and for the gym-based group was 67.2% ± 5. The average RPE and affect during exercise was for both groups 12 ± 1 ("somewhat hard") and 3 ± 1 ("good"), respectively. During the 6-month exercise intervention period for both groups, the exercise-induced symptoms were minimal to none. The user suitability evaluation questionnaire revealed that the online real time telerehabilitation and tele coaching programme was enjoyable (4.85 ± 0.37) and did not induce general discomfort (1.20 ± 0.41). Conclusion Our cardiac telerehabilitation programme seems to be feasible, acceptable, safe, and enjoyable for people with a recent MI. Our participants had an overall positive experience and acceptability of the cardiac telerehabilitation and tele coaching using wearable devices. Trial registration ClinicalTrial.gov, ID NCT06071273, 10/02/2023, retrospectively registered.